Aromaticity and Chirality: New Facets of Old Concepts - Bagrat A. Shainyan (Molecules, 2024)
The review summarizes the results of previous and the latest studies on aromaticity and related concepts. The electron counting rule for 3D-aromatic systems 2(n + 1)2 is shown to be a generalization of the 4n + 2 rule for planar molecules, and, vice versa, the latter can be derived from the former. The relative stability of the push–pull and captodative aromatic systems is shown to depend on the nature of the groups separated by the C=C bond in geminal or vicinal positions. The fully symmetrical molecules of hexamethylbenzene and hexacyanobenzene were studied using structural, energetic, and NMR criteria, and the donor substituents were shown to increase the aromaticity. Taking into account the coincidence of the number of π-electrons in aromatic systems with the number of electrons on the filled electron subshells (s, p, d, and f) and considering electrons as objects in a space of states allowed to conclude that no g-elements can exist and that the extension of the Periodic Table is possible only by filling 6f, 7d, or 8s subshells. The dimensionality of space also affects the chirality of molecules, making planar or even linear molecules chiral on oriented surfaces, which can be used for the preparation of enantiomerically pure drugs, resolution of prochiral compounds, etc.